Formulation Optimization of Coconut Oil Complex Gel Fudge and the Effect of Storage Time on Its Textural Properties - Shumin LIU; Xiaodan CHEN; Kailin ZENG; Xiaojun HU (Shipin gongye ke-ji, 2023)
In order to broaden the application of coconut oil, virgin coconut oil, gelatin and pectin were used to prepare complex gel fudge. The optimal formulation of coconut oil complex gel fudge was obtained via single-factor test and orthogonal tests with sensory score as evaluation index, and the effect of storage time on the texture of gel fudge was also investigated. The results showed that the optimal technological parameters of coconut oil complex gel fudge were as follows: Coconut oil 9.44 g, total sugar 34.00 g, total gum 35.89 g, among which the mass ratio of maltose, xylitol and brown sugar was 24:5:5, the mass ratio of total sugar and total gum was 36:38, and the mass ratio of coconut oil and sugar gum was 10:74. The complex gel fudge prepared under this formula had rich coconut flavor, smooth and non-sticky, proper sweetness, and the sensory score was 84.22±1.17. Results of texture analysis showed that the hardness, gumminess and chewiness of the coconut oil complex gel fudge increased extremely significantly with the extension of storage time (P<0.01), but the elasticity did not change significantly (P>0.05). This study provides references for coconut oil utilization.